PENGARUH PERSEPSI KUALITAS PELAYANAN DAN KOMUNIKASI TERHADAP KEPUASAN MAHASISWA DI BIRO KEMAHASISWAAN IBI DARMAJAYA - -, Helmita (Jurnal Manajemen Magister Darmajaya, 2016)
This research aimed to determine the effect of service quality perceptions and communication to the satisfaction of Student Affairs in IBI Darmajaya Bandar Lampung. The samples were students which followed the organizationÂ  in IBI Darmajaya as many as 87 students, taken by using random sampling technique. The data analysis included: data validity test, reliability test, normality test, linearity test, homogenity test, multiple regression analysis, multicolinearity, heteroskadasity test, autocorrelation test, t test, andÂ  F test. The results showed that an independent variable, service quality perception (X1) affected on studentsâ satisfaction (Y) at Student Affairs in IBI Darmajaya. A service quality perception variable (X1) partially significant affected on student sâ satisfaction (Y). The student affairs has not provided services based onÂ  needs and expectations, because there were still found any complaints and criticism about services at student affairs. Students hadÂ  perceptions that quality of services at bureau of student affairs were considered poor since the correlation coefficient indicatedÂ  the level of relationship between the variables was 0.902. It meant there was a very strong effect among the variables and it would affect positively between variables. However, the determination coefficient indicated that the degree of effect was 0.810, andÂ  it was explained that the studentsâ satisfaction variable (Y) was affected by the variable of service quality perceptions (X1) and communications (X2) as much as 0.814 or 81.4% andÂ  the remainder as much as (1-.81) = 0.19 or 19%, which was affected by other variables observed.Â Keywords: Service Quality Perception, Communication, Satisfaction, Student Affairs